Los desafíos de la emigración centroamericana en el Siglo XXI - Manuel Ángel Castillo (Les Cahiers ALHIM)
This essay presents the recent migration problems Central American populations. It analyses how, after the armed conflicts of the seventies and eighties, the migration patterns of these populations were modified forcing them to move to other countries inside and outside the region. After this period, a part of the concerned populations settle and integrated themselves in some of the receiving countries such as Mexico and the United States. Two main points are discussed, the growing importance economic factors play on the migration process of Central Americans as well as the political control used by the governments of the two countries.